Seed lipases: sources, applications and properties - a review - Barros, M.; Fleuri, L. F. [UNESP]; Macedo, G. A. (Brazilian Soc Chemical Eng, 2010)
This paper provides an overview regarding the main aspects of seed lipases, such as the reactions catalyzed, physiological functions, specificities, sources and applications. Lipases are ubiquitous in nature and are produced by several plants, animals and microorganisms. These enzymes exhibit several very interesting features, such as low cost and easy purification, which make their commercial exploitation as industrial enzymes a potentially attractive alternative. The applications of lipases in food, detergents, oils and fats, medicines and fine chemistry, effluent treatment, biodiesel production and in the cellulose pulp industry, as well as the main sources of oilseed and cereal seed lipases, are reviewed.
Keywords: Vegetable Lipases; Reactions; Sources; Application